Phân lập vi khuẩn phân hủy toluene và khảo sát khả năng phân hủy hỗn hợp hydrocarbon thơm trong nước thải phòng thí nghiệm. - Thi, Phi Oanh Nguyen (2025)
Toluene is an aromatic hydrocarbon commonly used as a solvent in industry and as one of the main components of gasoline. Due to its solubility in water, the compound may accumulate in surface water or reachgroundwater causing harmful effects on human health. Twenty bacterial strains grown on a minimal medium supplemented with toluene as the sole carbon source were isolated from the sediment samples of a laboratory wastewater treatment system. Among these, strains TL5 and TL27 performed toluene degradation capability